Peran Posyandu Lansia Dalam Mensejahterakan Lansia di Desa Gunung Bandung Kecamatan Lima Puluh Kabupaten Batu Bara - Nur Azizah Siregar; Ramadan Lubis; Annisa Annisa; Safrina Putri Pasaribu; Padia Azzahra Hutasuhut; Maulup Rampali Simbolon (Badan Penerbit STIEPARI Press, 2024)
Elderly is a condition where a person experiences a gradual process of change. Changes experienced by the elderly include physical or health, biological, cognitive, social psychological and economic changes. In general, the elderly have very significant health or physical changes, the elderly will experience a decrease in health and are susceptible to disease if they do not have an understanding of their body condition. The elderly Posyandu was established to provide health checks and education to the elderly and their families to pay more attention to the condition of the elderly. The purpose of this study is to explain the role of the posyandu's role on the elderly, to what extent the welfare of the elderly is after the existence of the elderly posyandu in Gunung Bandung village.